2007
DOI: 10.1002/aoc.1246
|View full text |Cite
|
Sign up to set email alerts
|

Dicoumarol complexes of Cu(II), Fe(II) and Fe(III): preparation, characterization, in‐vitro antibacterial and DNA binding activity

Abstract: were synthesized and characterized using 1 H-NMR, 13 C-NMR, IR spectra, electronic spectra, magnetic measurements and elemental analyses. The ligands, metal salts, complexes, control and standard drug were tested for their in-vitro antibacterial activity against Bacillus cereus, Staphylococcus aureus, Escherichia coli, Bacillus subtilis, Salmonella typhi, and Serratia marcescens. The metal complexes exhibit good activity against bacterial strains compared with parental compounds and moderate compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Their complexation ability in respect to different metal ions has been studied and discussed widely in a considerable number of investigations [5][6][7][8][9]. It has been found that the binding of a metal to the coumarin moiety retains or even enhances its biological activity [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Their complexation ability in respect to different metal ions has been studied and discussed widely in a considerable number of investigations [5][6][7][8][9]. It has been found that the binding of a metal to the coumarin moiety retains or even enhances its biological activity [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The ν(C O) peak for A 5 , A 7 and A 8 was observed at ∼1680 cm −1 (cyclic) and ∼1660 cm −1 (acetyl), which was shifted to 1574 cm −1 on formation of complexes. 30 These data were further supported by a ν(M-O) 25 band appearing at ∼510 cm −1 . The band at ∼1478 cm −1 was assigned to δ(C-H) bending of <N-CH 2 -CH 2 -N →.…”
Section: Ir Spectramentioning
confidence: 85%
“…The biocidal activities of the ofloxacin, levofloxacin, flucanozole, ligands, metal salts and their complexes were analyzed against various Gram-negative and Gram-positive bacterial cultures of Staphylococcus aureus, Bacillus subtilis, Bacillus cereus, Salmonella typhi, Escherichia coli and Serratia marcescens using the Agar-plate technique. 16,25…”
Section: Biocidal Activity Assaymentioning
confidence: 99%
“…[109] In addition, some dicoumarol complexes of Cu (II), Fe (II) and Fe (III), La (III), and Ag (I) have biological activity. [110] Recently, it was established that the cell killing and oxidative stress in pancreatic cancer cells was initiated by inhibition of NAD(P)H:quinone oxidoreductase (NQO1) with biscoumarins. [111] This biologically important moiety can be easily synthesized by the reaction of 4hydroxycoumarin and various aldehydes in the presence of various homogeneous and heterogeneous catalysts.…”
Section: Chemistryselectmentioning
confidence: 99%